2020
DOI: 10.1111/jog.14570
|View full text |Cite
|
Sign up to set email alerts
|

Can placental elasticity predict the time of delivery in cases of threatened preterm labor?

Abstract: Aim We aimed to evaluate placental elasticity for the short‐time prediction of delivery in cases of threatened preterm labor (TPL). Methods We performed a prospective study with consented pregnant women diagnosed with TPL (24th to 34th gestational week). According to the birth time, the patients were grouped into two groups, whether the delivery happened in the following first week or not. We compared the placental strain ratio (PSR) values between these two groups. Results A total of 108 pregnant women divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Elastography, a non-invasive tool that can measure tissue stiffness, has been used with EUS as an integrated software [51,52]. The use of EUS elastography for the evaluation of the pancreas was first reported in 2006 [53].…”
Section: Real-time Elastography-endoscopic Ultrasoundmentioning
confidence: 99%
“…Elastography, a non-invasive tool that can measure tissue stiffness, has been used with EUS as an integrated software [51,52]. The use of EUS elastography for the evaluation of the pancreas was first reported in 2006 [53].…”
Section: Real-time Elastography-endoscopic Ultrasoundmentioning
confidence: 99%
“…[8][9][10][11] Placental elasticity is also being studied to predict the time of delivery in threatened preterm labour and on intraoperative bleeding in post-caesarean pregnant women. 12,13 The first report on cervical elastography during pregnancy was published in 2007. 7 Two types of cervical elastography have been developed for quantitative determination of stiffness of pregnant cervixstrain elastography and shear wave elastography.…”
Section: Quantitative Sonoelastography Of the Uterine Cervix In Predi...mentioning
confidence: 99%
“…Tolunay et al conducted a prospective study of threatened preterm labor (TPL) ( n = 108) and measured PSR values. Multivariate logistic regression analysis showed that when the PSR value was 4.04, the sensitivity of short-term delivery time prediction was 77.78%, and the specificity was 87.04% [ 83 ]. SE may contribute to predict delivery time in TPL high-risk pregnancies.…”
Section: Predicting Preterm Deliverymentioning
confidence: 99%